2021
DOI: 10.3390/cancers13215481
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic KRAS-Induced Feedback Inflammatory Signaling in Pancreatic Cancer: An Overview and New Therapeutic Opportunities

Abstract: Pancreatic ductal adenocarcinoma (PDAC) remains highly refractory to treatment. While the KRAS oncogene is present in almost all PDAC cases and accounts for many of the malignant feats of PDAC, targeting KRAS or its canonical, direct effector cascades remains unsuccessful in patients. The recalcitrant nature of PDAC is also heavily influenced by its highly fibro-inflammatory tumor microenvironment (TME), which comprises an acellular extracellular matrix and various types of non-neoplastic cells including fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 172 publications
0
8
0
Order By: Relevance
“…Mutations in the KRAS oncogene are present in >90% of PDAC patients and activation of this pathway defines the disease [ 57 , 58 , 59 ]. Mutated KRAS in combination with inflammation or loss of key tumor suppressors drives progression of pre-malignant lesions to PDAC and is implicated in the recruitment of an immunosuppressive cellular milieu through KRAS-driven production of pro-inflammatory cytokines and chemokines [ 60 , 61 , 62 , 63 ]. Oncogenic KRAS has also been implicated in tumor immune evasion [ 64 , 65 ].…”
Section: Pdac Is Defined By An Immunosuppressive Tmementioning
confidence: 99%
“…Mutations in the KRAS oncogene are present in >90% of PDAC patients and activation of this pathway defines the disease [ 57 , 58 , 59 ]. Mutated KRAS in combination with inflammation or loss of key tumor suppressors drives progression of pre-malignant lesions to PDAC and is implicated in the recruitment of an immunosuppressive cellular milieu through KRAS-driven production of pro-inflammatory cytokines and chemokines [ 60 , 61 , 62 , 63 ]. Oncogenic KRAS has also been implicated in tumor immune evasion [ 64 , 65 ].…”
Section: Pdac Is Defined By An Immunosuppressive Tmementioning
confidence: 99%
“…YAP1 is the critical transcription factor in the Hippo signalling pathway and is known to be involved in cell proliferation, EMT, tumour invasion and metastasis. KRAS activation is present in almost all PDAC cases and accounts for many malignant features of PDAC 35. YAP1 not only cooperates with KRAS in PDAC initiation but can also substitute for oncogenic KRAS in advanced PDAC 20–23.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, this study demonstrated that high-risk individuals had high frequencies of KRAS and TP53 mutations and increased Th2 cell infiltration in cancerous tissues. Oncogenic KRAS mutations have been confirmed to participate in fibro-inflammatory microenvironment development, tumorigenesis, and growth in PC [94,128]. Wormann et al [129] discovered that TP53 mutation or absence of p53 function in pancreatic tumors of mice activates the JAK2-STAT3 signaling pathway, which reduces fibrosis and the abundance of stellate cells in the stroma of pancreatic tumors and alters the types of immunocyte infiltration, promoting tumor growth, and stroma modification.…”
Section: Discussionmentioning
confidence: 99%